Ethyl 2-[4-(4-chlorobenzoyl)phenoxy]-2-methylpropanoate - Yang, Zhao (International Union of Crystallography, 2012)
In the title compound, C(19)H(19)ClO(4), the dihedral angle between the mean planes of the benzene rings is 126.8 (1)°. Weak C—H⋯O interactions are observed.